The Implementation of Social Issue-Based Social Studies Learning: A Qualitative Case Study at SMP Negeri 2 Sungai Melayu Rayak - Siswati; Siswandi; Karel Juniardi (Yayasan Ilomata, 2026)
This study examines the implementation of social issue-based Social Studies learning at SMP Negeri 2 Sungai Melayu Rayak in response to the limited contextualization of Social Studies instruction, which remains predominantly content-oriented despite curriculum reforms promoting student-centered learning. Previous studies have largely emphasized the theoretical importance of social issue-based learning, while empirical evidence regarding its classroom implementation in Indonesian junior secondary schools remains limited. Using a qualitative case study design, data were collected through in-depth interviews with teachers, school leaders, and students, alongside classroom observations and document analysis of lesson plans and instructional materials. The data were analyzed through data reduction, data display, and thematic conclusion drawing. The findings reveal that the integration of local social issues, including agrarian conflicts and environmental problems, was associated with enhanced instructional relevance and encouraged active student participation. Learning activities based on group discussion, case analysis, and reflective presentation were perceived to support students’ critical thinking, argumentation, and collaborative abilities. The study also found that the Kurikulum Merdeka framework provided pedagogical flexibility that enabled teachers to adapt learning materials to students’ social realities. This study contributes to the literature by demonstrating how social issue-based Social Studies learning can be operationalized in a local Indonesian school context to foster contextual critical awareness and civic responsibility among junior secondary students.